Linkage disequilibrium (LD) analysis of schizophrenia (SC) and schizoaffective disorder (SA) in the Costa Rican population: preliminary findings on chromosome 13 - Escamilla, Michael A. (2001)
As the first step in a genome-wide LD screen for SC genes in the Costa Rican population, we report here a preliminary analysis of chromosome 13. Subjects were drawn from the Central Valley of Costa Rica (CVCR), an ideal population for LD mapping of psychiatric disorders (Escamilla et al. 1996). Best estimate consensus diagnoses were made using information from DIGS, FIGS and medical records. ABI LMSV2 markers were used to genotype 102 persons with DSMIV diagnosis of SC or SA, and 189 control chromosomes. Two statistical tests appropriate for model-free LD mapping were used: the CLUMP test of Sham and Curtis and the likelihood association test of Terwilliger. Evidence of LD was found at two contiguous markers in the 13q region (P = .06 at D13S1263 and P = .01 at D13S173). We next genotyped three additional markers near D13S263 and D13S173. One of these (D13S286) showed additional evidence of LD (P = .03). The markers which showed possible LD span a 5.8 cM region which lies within the larger region previously reported to be linked to a gene for SC/S A disorder in a North American population (Blouin et al. 1998). Although results of this magnitude must be interpreted with caution, these preliminary results support the possibility of a SC/SA gene being in the 13q region. Future analyses (including haplotype analyses) with a larger sample from the CRCV should prove useful in proving whether SC/SA predisposition genes are indeed present in this population as well as in providing finer localization of the putative 13q SC/SA gene.